PENGARUH MENDENGARKAN AL-QUR’AN TERHADAP PERUBAHAN TEKANAN DARAH PADA LANSIA PENDERITA HIPERTENSI DIWILAYAH PUSKESMAS ANDALAS PADANG TAHUN 2018 - Lola Despitasari (JURNAL KESEHATAN MERCUSUAR, 2019)
Hypertension occurs mostly in the elderly because of the increasing age of a person, the body will experience a decrease in both function and structure such as atherosclerosis, reduced elasticity, and a decrease in vascular smooth muscle relations that can reduce cardiac output and increase peripheral resistance resulting in hypertension. The purpose of this study was to determine the effect of Al-Qur'an listening therapy on changes in blood pressure in elderly who experience hypertension.This type of research is pre-experimental with the design of one group pretest-posttest design. Data collection was carried out on July 16 2018 - July 25 2018 in Andalas Community Health Center Padang. The number of samples was 11 people who were taken using purposive sampling technique. Data processing with Paired Sample T-test. The results showed that the mean value of systolic and diastole blood pressure before being given Al-Qur'an listening therapy was 159 mmHg and 90.09 mmHg and after giving Al-Qur'an listening therapy, the mean value of systolic and diastolic blood pressure was 149.27 mmHg and 81 mmHg. Paired sample T-test test showed that p value = 0.000 means that Al-Qur'an listening therapy affects changes in blood pressure in elderly who experience hypertension. Based on the results of the above studies, listening to the Qur'an influences blood pressure changes in elderly people who experience hypertension and is advised for health workers to inform the importance of listening to the Qur'an to control blood pressure values ​​in the prevention of complications. Keyword : Blood Pressure, Brisk walking exercise, Hypertension